2022
DOI: 10.1021/acs.organomet.2c00413
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Dehydrogenation of Liquid Organic Hydrogen Carrier Model Compounds by CpM+ (M = Fe, Co, Ni) in the Gas Phase

Abstract: Although there is much interest in developing liquid organic hydrogen carriers (LOHCs) and new metal catalysts to release hydrogen on demand for application in energy generation, few studies have provided mechanistic insights into the crucial metal-catalyzed dehydrogenation reactions. Here we use multistage mass spectrometry experiments and DFT calculations to examine the dehydrogenation of the LOHC model compounds cyclohexane, pyrrolidine, N-methylpyrrolidine, and piperidine by the half-sandwich cyclopentadie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…The 28 pre-aromatic N-heterocycles included 6H 2 (−0.4 kcal mol −1 ), 7H 2 (−0.8 kcal mol −1 ), 8H 2 (2.9 kcal mol −1 ), 15H 2 (2.7 kcal mol −1 ), 23H 2 (−1.9 kcal mol −1 ), 24H 2 (0.6 kcal mol −1 ), 29H 2 (1.9 kcal mol −1 ), 30H 2 (−0.2 kcal mol −1 ), 31H 2 (3.5 kcal mol −1 ), 32H 2 (−0.1 kcal mol −1 ), 38H 2 (0.7 kcal mol −1 ), 40H 2 (2.8 kcal mol −1 ), 41H 2 (0.8 kcal mol −1 ), 46H 2 (−2.5 kcal mol −1 ), 48H 2 (−1.1 kcal mol −1 ), 49H 2 (0.2 kcal mol −1 ), 51H 2 (−0.1 kcal mol −1 ), 52H 2 (−1.3 kcal mol −1 ), 53H 2 (3.0 kcal mol −1 ), 61H 2 (0.3 kcal mol −1 ), 64H 2 (−2.3 kcal mol −1 ), 65H 2 (−1.4 kcal mol −1 ), 66H 2 (1.6 kcal mol −1 ), 68H 2 (2.4 kcal mol −1 ), 70H 2 (0.6 kcal mol −1 ), 72H 2 (1.0 kcal mol −1 ), 76H 2 (2.2 kcal mol −1 ), and 78H 2 (0.9 kcal mol −1 ), which need further validation and support in experimental work. Examining the chemical structures of the investigated N-heterocycles in previous literature, 3–19 they were not exactly the same pre-aromatic N-heterocycle structure, and most cases involved two H 2 molecules release and acceptance from N-heterocycles, which could not provide direct experimental data to validate the thermodynamic model.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The 28 pre-aromatic N-heterocycles included 6H 2 (−0.4 kcal mol −1 ), 7H 2 (−0.8 kcal mol −1 ), 8H 2 (2.9 kcal mol −1 ), 15H 2 (2.7 kcal mol −1 ), 23H 2 (−1.9 kcal mol −1 ), 24H 2 (0.6 kcal mol −1 ), 29H 2 (1.9 kcal mol −1 ), 30H 2 (−0.2 kcal mol −1 ), 31H 2 (3.5 kcal mol −1 ), 32H 2 (−0.1 kcal mol −1 ), 38H 2 (0.7 kcal mol −1 ), 40H 2 (2.8 kcal mol −1 ), 41H 2 (0.8 kcal mol −1 ), 46H 2 (−2.5 kcal mol −1 ), 48H 2 (−1.1 kcal mol −1 ), 49H 2 (0.2 kcal mol −1 ), 51H 2 (−0.1 kcal mol −1 ), 52H 2 (−1.3 kcal mol −1 ), 53H 2 (3.0 kcal mol −1 ), 61H 2 (0.3 kcal mol −1 ), 64H 2 (−2.3 kcal mol −1 ), 65H 2 (−1.4 kcal mol −1 ), 66H 2 (1.6 kcal mol −1 ), 68H 2 (2.4 kcal mol −1 ), 70H 2 (0.6 kcal mol −1 ), 72H 2 (1.0 kcal mol −1 ), 76H 2 (2.2 kcal mol −1 ), and 78H 2 (0.9 kcal mol −1 ), which need further validation and support in experimental work. Examining the chemical structures of the investigated N-heterocycles in previous literature, 3–19 they were not exactly the same pre-aromatic N-heterocycle structure, and most cases involved two H 2 molecules release and acceptance from N-heterocycles, which could not provide direct experimental data to validate the thermodynamic model.…”
Section: Resultsmentioning
confidence: 93%
“…From Scheme 5, the following valuable conclusions could be made: (1) the Δ G H 2 R ( Y I H 2 ) scale covered from −15.8 kcal mol −1 to 22.0 kcal mol −1 , which spanned the widest thermodynamic range by 37.8 kcal mol −1 among the 4 groups of amines Y I H 2 –Y IV H 2 ; (2) according to the Δ G H 2 R ( YH 2 ) scales of Y II H 2 (−11.5 to 8.5 kcal mol −1 ), Y III H 2 (−7.4 to 9.5 kcal mol −1 ), and Y IV H 2 (10.3–18.3 kcal mol −1 ), the dehydrogenation abilities decreased in the order of Y II H 2 ≈ Y III H 2 > Y IV H 2 ; (3) in view of the relations between sets, it was found that the Δ G H 2 R ( YH 2 ) values displayed the following regular pattern of {Δ G H 2 R ( Y II H 2 ) ∪ Δ G H 2 R ( Y III H 2 ) ∪ Δ G H 2 R ( Y IV H 2 )} ⊆ Δ G H 2 R ( Y I H 2 ); (4) for the pre-aromatic N-heterocycles, the Δ G H 2 R ( YH 2 ) scales ranged from −15.8 to 22.0 kcal mol −1 for Y I H 2 , from −11.5 to 8.5 kcal mol −1 for Y II H 2 , and from −7.4 to 9.5 kcal mol −1 for Y III H 2 , respectively. Since the Δ G H 2 R ( YH 2 ) scales of Y I H 2 , Y II H 2 , and Y III H 2 crossed negative and positive values (−15.8 to 22.0 kcal mol −1 ), it was indicated that not all the acceptorless dehydrogenation of pre-aromatic N-heterocycles is a thermodynamically uphill or downhill process under ambient conditions, 3–19 and not all pre-aromatic N-heterocycles are thermodynamically feasible to serve as chemical hydrogen-storage materials. Δ G H 2 R ( YH 2 ) is absolutely an important thermodynamic parameter to guide chemists to discover more potentially excellent chemical hydrogen-storage materials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations